Journeying into Academia via Immersion into Qualitative Research: Professor Shaffir as a Master Guide - Etoroma, Efa E. (Qualitative Sociology Review, 2020)
The choice of a work career is one of the most important events in a person’s life course and typically involves secondary socialization and identification with role models. This paper is concerned with the crucial role of my PhD dissertation supervisor at McMaster University, Dr. Billy Shaffir, in my choice of an academic career. I highlight and celebrate how, through the guidance of Dr. Shaffir, I experienced “immersive socialization” into field research and happily converted from an intended business career to an academic career.